Mortality profile of extreme to very preterm infants in an extramural tertiary care neonatal unit of a teaching hospital in Southern India: a retrospective study - Shanmugam, Ramya S.; Karthik, Arun; N., Muthukumaran; Kamalarathanam, Chinnathambi (International Journal of Contemporary Pediatrics, 2020)
Background: Neonatal deaths account for 47% of all deaths in children younger than 5 years globally. More than a third of deaths are due to preterm related complications. Understanding the factors contributing to preterm deaths and pattern of mortality is needed to implement interventions that are essential in improving neonatal survival. Methods: This was a retrospective study done in neonatal intensive care unit, Institute of Child Health (ICH) and Hospital for Children, Chennai, a tertiary care regional center. All preterm (<32 weeks) deaths registered in the neonatal medical records from 1st of January 2018 to 31st of December 2018 were analysed. Primary causes of deaths were analysed by two consultants. When there were more than one cause contributing to responsible for death the most significant problem was taken as the cause of death. Results: Overall neonatal mortality was 312 (14.2%) of 2189 neonates. Out of 148 admissions in the study population mortality was 74.2% (26 of 35) for extreme preterm (<28 weeks) infants and 42.7% (48 of 113) for very preterm (28 to 32 weeks) infants. Predominant causes of death were sepsis 44.5% (33), prematurity-related complications 37.8% (28) followed by congenital anomalies 12.1% (9) and miscellaneous causes 2.7% (2). Respiratory Distress Syndrome (RDS) and Intra Ventricular Haemorrhage (IVH) attributed to 75% (21/ 28) of deaths among prematurity-related complications. Conclusions: This study identified sepsis; prematurity related complications were the predominant causes of mortality in the extreme to very preterm population. Understanding the specific causes of preterm mortality would help to implement interventions to promote their survival.